Identifikasi Kemampuan Berbagai Jenis Green Infrastructure dalam Upaya Mengurangi Banjir pada Das Ciliwung Hilir DKI Jakarta - Farizzy Priscannanda; Hilwati Hindersah (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The flood disaster due to the overflow of the Ciliwung River is a disaster that regularly occurs in the capital city of the Republic of Indonesia, the city of Jakarta. Based on a quantitative research approach, the stage carried out in this study is to determine the problems that occur in the field. From this analysis stage, it was identified the type of green infrastructure in the form of a vegetated filter strip covering an area of 10,114.31 Ha, a retention pond and a detention pond each covering an area of 11,650.62 Ha to be applied to the Ciliwung Hilir watershed of DKI Jakarta. The result of this study are the application of vegetated filter strips in Cakung District, East Jakarta covering an area of 1,469.5 Ha; a detention pond in Cengkareng District, West Jakarta covering an area of 989.9 ha; and retention ponds in 10,527 flood-prone RTs spread throughout DKI Jakarta with a total area of 412 Ha. The last analysis stage is calculating the level of capability of the three types of green infrastructure in reducing the flood volume of the Ciliwung River based on the capacity of each type, based on the Log Pearson III frequency distribution method, with results: a vegetated filter strip with an area of is able to reduce the volume of flooding by 27,100,656.6 m3; the detention pond is able to reduce the flood volume by 27,755,808.8 m3; and retention ponds are able to reduce inundation by 20,615,400 m3. Abstrak. Musibah banjir akibat luapan Sungai Ciliwung merupakan musibah yang rutin terjadi di Ibukota Negara Republik Indonesia, Kota Jakarta. Berlandaskan pendekatan penelitian kuantitatif, tahapan yang dilakukan dalam penelitian ini yaitu menentukan permasalahan yang terjadi di lapangan. Dari tahap analisis ini teridentifikasi jenis green infrastructure berupa vegetated filter strip seluas 10.114,31 Ha, kolam retensi dan kolam detensi masing-masing seluas 11.650,62 Ha untuk diterapkan pada DAS Ciliwung Hilir DKI Jakarta. Hasil dari penelitian ini yaitu penerapan vegetated filter strip di Kecamatan Cakung, Jakarta Timur seluas 1.469,5 Ha; kolam detensi di Kecamatan Cengkareng, Jakarta Barat seluas 989,9 Ha; dan kolam retensi di 10.527 RT rawan banjir yang tersebar di seluruh DKI Jakarta dengan total luas 412 Ha. Tahap analisis terakhir yaitu perhitungan tingkat kemampuan ketiga jenis green infrastructure dalam mengurangi volume banjir Sungai Ciliwung berdasarkan kemampuan daya tampung masing-masing jenisnya, berdasarkan metode distribusi frekuensi Log Pearson III, dengan hasil: vegetated filter strip seluas mampu mengurangi volume banjir sebesar 27.100.656,6 m3; kolam detensi mampu mengurangi volume banjir sebesar 27.755.808,8 m3; dan kolam retensi mampu mengurangi genangan sebesar 20.615.400 m3.